2018
DOI: 10.1007/s40279-018-0892-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of Foundational Movement Skills: A Conceptual Model for Physical Activity Across the Lifespan

Abstract: Evidence supports a positive association between competence in fundamental movement skills (e.g., kicking, jumping) and physical activity in young people. Whilst important, fundamental movement skills do not reflect the broad diversity of skills utilized in physical activity pursuits across the lifespan. Debate surrounds the question of what are the most salient skills to be learned which facilitate physical activity participation across the lifespan. In this paper, it is proposed that the term 'fundamental mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
277
0
21

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 309 publications
(311 citation statements)
references
References 54 publications
13
277
0
21
Order By: Relevance
“…FMS are significantly correlated with high levels of physical activity and fewer health concerns among youth with TD (Lubans et al 2010;Holfelder & Schott 2014;Logan et al 2015;Barnett et al 2016b;Hulteen et al 2018), and FMS interventions improved FMS proficiency (Tompsett et al 2017). Given that children and adolescents with ID tend to present deficits in FMS, which may persist as the youth develop, improvement of FMS components (i.e.…”
Section: Implications For Practicementioning
confidence: 99%
“…FMS are significantly correlated with high levels of physical activity and fewer health concerns among youth with TD (Lubans et al 2010;Holfelder & Schott 2014;Logan et al 2015;Barnett et al 2016b;Hulteen et al 2018), and FMS interventions improved FMS proficiency (Tompsett et al 2017). Given that children and adolescents with ID tend to present deficits in FMS, which may persist as the youth develop, improvement of FMS components (i.e.…”
Section: Implications For Practicementioning
confidence: 99%
“…The development of MC constitutes a foundation for human motor behavior as these skills are noted as both direct and indirect building blocks for a multitude of lifetime activities . The development of a strong foundation of MC requires the development of coordination and control of complex multisegmental movements that are grouped according to their focus on stability, locomotion, and manipulation/projection of objects .…”
Section: Introductionmentioning
confidence: 99%
“…Among children and adolescents with TD, FMS have been considered particularly important for promoting physical activity participation and, by extension, for inducing health benefits (Hulteen, Morgan, Barnett, Stodden, & Lubans, 2018). Indeed, several systematic reviews have indicated a positive association between FMS and physical activity among children with TD (Holfelder & Schott, 2014;Logan, Webster, Getchell, Pfeiffer, & Robinson, 2015; Lubans, Morgan, Cliff, Barnett, & Okely, 2010).…”
Section: Introductionmentioning
confidence: 99%